HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI UNTUK SEMBUH PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI DI RSU. IMELDA PEKERJA INDONESIA - Nataria Yanti Silaban; Edisyah Putra Ritonga (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
Cancer is the growth of abnormal cells that tend to attack the surrounding tissue and spread to other organs of the body that are far away. Cancer patients undergoing chemotherapy sometimes feel pessimistic that their disease cannot be overcome or cannot be cured, to reduce this pessimism family support is needed so that patients have the motivation to recover.. motivation to recover in cancer patients undergoing chemotherapy at The Imelda Indonesian Workers General Hospital in 2020. This study uses a descriptive correlation design with a cross-sectional approach, with a population of 30 people and sampling with non-probability sampling methode using purposive sampling. The data analysis technique used univariate and bivariate data analysis with a significant level of 95% (≤ 0.05). The results of this study indicate that there is asignificant relationship between family support and motivation to recover in cancer patients undergoing chemotherapy with P value = 0.05 at the Imelda General Hospital of Indonesian Workers in 2020. Based on the results of the study, it is expected that health workers and researchers can understand and improve the quality of nursing care by involving families to motivate patient to willing to undergoing chemotherapy regularly in the working area of the Imelda Indonesian Workers General Hospital in 2021.